2013
DOI: 10.1002/jbio.201300119
|View full text |Cite
|
Sign up to set email alerts
|

In vivo pump‐probe optical coherence tomography imaging in Xenopus laevis

Abstract: Currently, optical coherence tomography (OCT), is not capable of obtaining molecular information often crucial for identification of disease. To enable molecular imaging with OCT, we have further developed a technique that harnesses transient changes in light absorption in the sample to garner molecular information. A Fourier-domain Pump-Probe OCT (PPOCT) system utilizing a 532 nm pump and 830 nm probe has been developed for imaging hemoglobin. Methylene blue, a biological dye with well-know photophysics, was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…Previous studies have demonstrated melanin (93, 94), Phytochrome A (95), and hemoglobin (90) imaging via PPOCT. Recently, a two-color (532 nm pump, 830 nm probe) PPOCT system was utilized to image the microvasculature of Xenopus laevis in vivo, shown in Fig.…”
Section: Pump-probe Octmentioning
confidence: 99%
“…Previous studies have demonstrated melanin (93, 94), Phytochrome A (95), and hemoglobin (90) imaging via PPOCT. Recently, a two-color (532 nm pump, 830 nm probe) PPOCT system was utilized to image the microvasculature of Xenopus laevis in vivo, shown in Fig.…”
Section: Pump-probe Octmentioning
confidence: 99%
“…If we assume an impulse pump excitation, then N T is populated by intersystem crossing from S 1 with a quantum efficiency of q and immediately begins to decay, yielding N T qN S1 e −t∕τ where τ −1 is the decay rate back to the ground state, and the decay is assumed to be a single exponential. This approximation holds for short-pulsed pump lasers as in our previous work [5]. There we were able to measure τ for MB by varying the interpulse delay between the pump and probe to map out the decay and fit to a single exponential.…”
mentioning
confidence: 96%
“…In particular, MB has been shown to selectively stain specialized columnar epithelium in Barrett's esophagus [10]. Monitoring of Barrett's esophagus is one of the emerging clinical applications of OCT technology [11].Prior efforts [5,6] at imaging MB with PPOCT have utilized nanosecond pulsed lasers at 532 nm as the pump and femtosecond pulsed lasers at 830 nm as the probe. These succeeded in imaging tissue phantoms; however, there has never been a demonstration in a biological sample, either in vivo or ex vivo.…”
mentioning
confidence: 98%
See 2 more Smart Citations